Polynomial Factoring
Factor the following polynomial:
[tex]p\mleft(x\mright)=3x^3-4x^2+9x-12[/tex]Let's group the first two and the last two terms:
[tex]p(x)=(3x^3-4x^2)+(9x-12)[/tex]Factoring out x^2 from the first two terms and 3 from the last two terms
[tex]p(x)=x^2(3x-4)+3(3x-4)[/tex]Note the expression 3x-4 is common to both groups. Factoring it out:
[tex]p(x)=\mleft(3x-4\mright)(x^2+3)[/tex]The second factor is a sum of squares, so it cannot be factored further. The final factorization is:
[tex]p(x)=\mleft(3x-4\mright)(x^2+3)[/tex]